GERIATRIC NURSING CARE MANAGEMENT WITH A SERVICE EXCELLENCE APPROACH FOR MRS. J WITH GOUT ARTHRITIS AT THE UPTD SOCIAL SERVICES FOR THE ELDERLY, BINAJAI CITY, NORTHSUMATRA PROVINCE, YEAR 2025 - Jusnita; Sri Murtini; Adelina Florensia Br. Hutabarat; Erni Br Sirait; Prima Asna Olivia Febriyanti Pasaribu; Intan Putri Sinaga; Lilis Herlinda, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Elderly individuals represent a vulnerable group experiencing various functional declines, including an increased risk of degenerative diseases such as Gout Arthritis. This disease is characterized by severe joint pain caused by the accumulation of uric acid crystals, which disrupts daily activities and quality of life. This study aims to implement gerontic nursing care management based on service excellence in the case of Mrs. J, an elderly patient with Gout Arthritis at the UPTD Elderly Social Services Binjai. The research used a descriptive case study method, applying the nursing care process through assessment, diagnosis, planning, implementation, and evaluation. The assessment revealed that Mrs. J experienced acute pain, impaired physical mobility, and sleep disturbances due to inflammation and high uric acid levels (7 mg/dL). Interventions included both pharmacological and non-pharmacological therapies such as massage, education on a low-purine diet, and empathetic communication aligned with the principles of service excellence. The evaluation showed a decrease in pain scale, improvement in sleep quality, and enhanced mobility. This study concludes that implementing gerontic nursing care based on service excellence can improve comfort, independence, and quality of life in elderly patients with Gout Arthritis.